Read It and Weep: An Evaluation of People Involved in Avalanches and Their Forecast Reading Habits - Sarah Petelinsek; Rowan Kelner; Jamal Jones; Nikki Champion; Michael Morgan; Patrick G. Hughes (Wilderness & Environmental Medicine, 2026)
Introduction The aim of this investigation is to gain insight into how humans interact with the avalanche forecast and better understand the role that the avalanche forecast plays in prevention of human-triggered avalanche incidents. Methods Using a 5-y cross-sectional study of self-reported survey data of participants involved in avalanches, we performed a secondary analysis to identify trends and patterns in avalanche forecast reading habits. The study assessed avalanche forecast reading habits, perceptions, and retention of information as well as demographic information on participants. Results A total of 489 participants were included in the final analysis. Of all the respondents, 12% of people who report normally reading the avalanche forecast report not reading the forecast on the day of their avalanche involvement. The plurality of expert and authority users and people between the ages of 41 and 60 y skipped reading the avalanche forecast the day of their reported avalanche incident. Females were more likely than males to have not read the avalanche forecast the day of their avalanche involvement. Conclusions Although avalanche forecasts are widely used as a component of avalanche risk management, a meaningful proportion of individuals involved in avalanches reported not reading the forecast on the day of their incident. By understanding the forecast reading behavior of the people involved in avalanches, we can begin to design targeted efforts within the forecast aimed to decrease avalanche involvement, injury, and death.